Flood disaster preparedness of small and medium enterprises in Segamat, Johor, Malaysia - Hashim, Hajar Mariah (2019)
The role of SMEs in the contribution to economic development in any nation is acknowledged worldwide. However, due to their establishment, disaster can potentially and significantly affect SMEs sustainability in terms of performance and productivity, whether directly or indirectly. Specifically, floods disaster is one of the most common disaster which could cause various degrees of properties lost and damages of equipment, installation, building, business stock, etc. This is notwithstanding the extent of loss of businesses during closure of premise during and after the flood due to long term recovery. It has been generally attributed that most SMEs lack preparedness and were always caught unaware. On top of that, the complex nature of preparedness has also put SMEs in adverse position due to limited knowledge, resources, and workforce for proper and adequate disaster planning and preparedness. Thus, this study aims to develop a flood disaster preparedness index for SMEs in determining the flood disaster preparedness level and the factors associated with preparedness. The state of Johor was chosen for the field test in this study in light of the high distribution of SMEs wherein the district of Segamat was one of the flood-prone area. Using a questionnaire developed, validated by experts in disaster management through focus group discussion, and pretested, the interviewer-assisted questionnaire was conducted among the business owners and managers (n=337) of SMEs located at Segamat, Johor. Subsequently, Rasch model was used to validate the Flood Disaster Preparedness Action (FDPA) instrument. Half of the variance (50.5%) was explained based on the final validation of the FDPA from the sample population with inter-item consistency with Cronbach alpha values of 0.98. Expressed using Relative Importance Index (RII), it was found that the most significant flood impacts on SMEs (n=149) was customer and supplier supply being affected (RII = 0.739) amongst the 16 self-reported impacts of flood disaster. Subsequently, the flood preparedness data from SMEs were organized using Rasch model to create a preparedness index level. The analysis indicated that the SMEs preparedness level on flood disaster in this study can be divided into five levels: very high (10.3%), high (21